2015
DOI: 10.1038/srep16955
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Atoms from Methionines Interacting with Aromatic Residues Are Less Prone to Oxidation

Abstract: Methionine residues exhibit different degrees of susceptibility to oxidation. Although solvent accessibility is a relevant factor, oxidation at particular sites cannot be unequivocally explained by accessibility alone. To explore other possible structural determinants, we assembled different sets of oxidation-sensitive and oxidation-resistant methionines contained in human proteins. Comparisons of the proteins containing oxidized methionines with all proteins in the human proteome led to the conclusion that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 55 publications
8
45
0
Order By: Relevance
“…Although these analyses may seem redundant, they are not. For instance, in a previous work, we reported that sequences surrounding MetO do not exhibit a preference for neighbouring tyrosine residues30, which is in line with our observation that there is only a small proportion of MetO near pTyr when compared to Met. This observation confirms and extends our previous results, since we can now affirm that MetO, in addition to disliking Tyr, also seems to avoid pTyr (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Although these analyses may seem redundant, they are not. For instance, in a previous work, we reported that sequences surrounding MetO do not exhibit a preference for neighbouring tyrosine residues30, which is in line with our observation that there is only a small proportion of MetO near pTyr when compared to Met. This observation confirms and extends our previous results, since we can now affirm that MetO, in addition to disliking Tyr, also seems to avoid pTyr (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Met residues are highly susceptible to modification by mild oxidants8 and can be oxidized spontaneously during common experimental procedures9. In vitro Met oxidation is a reversible process1011 and is dependent upon solvent accessibility1213 and structural determinants1415. Met oxidation can also modify the physicochemical properties of the whole protein and therefore modulate its function1416.…”
mentioning
confidence: 99%
“…In vitro Met oxidation is a reversible process1011 and is dependent upon solvent accessibility1213 and structural determinants1415. Met oxidation can also modify the physicochemical properties of the whole protein and therefore modulate its function1416. However, the biological implications of the presence of oxidized Met in specific disease-related proteins have only been studied in limited numbers of human pathologies, including diabetes17, skin disease1011, Alzheimer’s disease18 and Parkinson’s disease19.…”
mentioning
confidence: 99%
“…In proteins, methionine residues are not equally sensitive to oxidation, but it appears that the surface-exposed ones are more sensitive to oxidation than the buried residues. Moreover, the amino acid environment determines the sensitivity to oxidation and the propensity to form one or the other diastereomer, although no sequence ‘signature’ of Met oxidation could be clearly defined [9,24,25]. Oxidation of Met in proteins can have several consequences (see [26,27] for reviews), and depending on these consequences, oxidized proteins can be classified into four groups [9]: (i) proteins not impaired by Met oxidation, which could fulfill, together with MSRs, an antioxidant function through cyclic oxidation and reduction of Met [28], (ii) proteins damaged by Met oxidation, such as those involved in neurodegenerative diseases [2931], (iii) unfolded proteins and nascent polypeptides whose protein core Met are susceptible to oxidation thereby affecting their proper folding which has been shown to greatly accelerate their degradation [9], and (iv) proteins whose functions are actively regulated by cyclic Met oxidation/reduction.…”
Section: Introductionmentioning
confidence: 99%